Experience capitalization - we are all in the same boat - Maikhuri, Anil (Technical Centre for Agricultural and Rural Cooperation, 2019)
Within development projects, the monitoring and evaluation and knowledge management systems are interlinked, and must be coordinated effectively to support project implementation. As we have seenin the Integrated Livelihood Support Project (ILSP) in Uttarakhand, India, both systems can be strengthened with experience capitalization, a process which involves the critical analysis of project experiences. Through a capitalization process, information gathered from a specific experience can be turned into institutional knowledge and utilised for improving project activities and impact